The role of body image perception, social media influence, and physical activity on eating behavior among Malaysian youth - Mohamad Arrif Emir, Widad Emir; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of body image perception, social media influence, and physical activity on eating behavior among Malaysian youth. A sample of 411 participants was employed using a quantitative approach to assess these variables through validated measures. Pearson correlation and multiple regression analyses were conducted to explore the relationships between the independent variables and eating behavior. The findings revealed that body image perception was the strongest negative predictor of unhealthy eating behavior, followed by physical activity, which contributed positively to healthy eating habits. Social media influence, on the other hand, was positively associated with disordered eating behaviors. These results emphasize the importance of promoting positive body image, encouraging regular physical activity, and addressing the adverse effects of social media in shaping healthy eating behavior. Policymakers, health educators, and mental health practitioners should focus on these areas to reduce disordered eating among youth. The study suggests implementing educational programs that promote body positivity, regulate harmful social media content, and encourage physical activity to foster healthier lifestyles among Malaysian youth.